2017
DOI: 10.1080/17470218.2016.1216574
|View full text |Cite
|
Sign up to set email alerts
|

Blocking by Fixed and Variable Stimuli: Effects of Stimulus Distribution on Blocking

Abstract: An experiment with rats compared the ability of fixed and variable duration cues to produce blocking. Rats in Group B (Blocking) were trained that both fixed-(F) and variable-(V) duration cues would be followed by food delivery. In a subsequent training stage F and V continued to be reinforced, but F was accompanied by X, and V by Y. In the test phase responding to X and Y was examined. Control Group O (Overshadowing) received identical treatment, except that F and V were nonreinforced in the first training st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…For example, it might for some reason have been easier to respond during a fixed-duration CS; however, we observed higher levels of responding to a cue trained with a fixed duration even when the animals were tested under identical conditions (Jennings et al, 2013). Furthermore, we also demonstrated that fixed-duration cues produce better overshadowing and better blocking than their variable counterparts (Bonardi, Mondragón, Brilot & Jennings, 2015; Jennings & Bonardi, 2017). Conditioning theories would interpret these findings as evidence that fixed-duration cues acquire more associative strength than variable CSs.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…For example, it might for some reason have been easier to respond during a fixed-duration CS; however, we observed higher levels of responding to a cue trained with a fixed duration even when the animals were tested under identical conditions (Jennings et al, 2013). Furthermore, we also demonstrated that fixed-duration cues produce better overshadowing and better blocking than their variable counterparts (Bonardi, Mondragón, Brilot & Jennings, 2015; Jennings & Bonardi, 2017). Conditioning theories would interpret these findings as evidence that fixed-duration cues acquire more associative strength than variable CSs.…”
Section: Introductionsupporting
confidence: 52%
“…Experiments 1 and 2 examined learning in a trace conditioning task, in which the CS was fixed, but the trace interval was either fixed or variable. In experiments using delay conditioning, we have observed higher levels of responding during a CS that is fixed than during one that is variable (Bonardi et al, 2015; Jennings et al, 2013; Jennings & Bonardi, 2017). We have argued here that this could either be due to the temporal distribution of the CS per se or to the fact that CS onset was only informative with respect to the time of food delivery in the fixed case.…”
Section: Discussionmentioning
confidence: 96%
“…These results indicate that taste experience specifically reduces the response variability during the palatability epoch—the epoch known to be critically impacted during CTA learning (Grossman et al, 2008; Moran and Katz, 2014; Arieli et al, 2022). Consistent with behavioral work showing enhanced learning with low conditioned stimulus variation (e.g., Jennings and Bonardi, 2017), the increase in across-trial reliability we see here may well make it easier for the rats to learn CTA. Another implication of this result is that, if each neuron in the ensemble is coding more reliably, the within-response transitions of ensemble code itself might be more coherent (see Jones et al, 2007; Sadacca et al, 2016).…”
Section: Resultssupporting
confidence: 88%
“…We hypothesized that the increase in discriminability may be tied to an increased reliability of pre-CTA sucrose responses (evident through higher signal-to-noise ratio (i.e., reduction of noise)). This hypothesis, if it is true, would (not incidentally) also explain how taste experience leads to LE of CTA learning because the reliability of the CS can critically impact the quality of associative learning (Jennings and Bonardi, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been used by others (e.g., Holland, 2000 ). An alternative approach to test the strength of learning, independent from performance effects, has been to assess the ability of the cues to restrict learning with other cues ( Bonardi et al, 2015 ; Jennings & Bonardi, 2017 ). For example, if cues differ in their strength of learning, then they should differ in their ability to block the acquisition or expression of conditioned responding with new cues.…”
Section: Discussionmentioning
confidence: 99%